Climate services bundles preferences of smallholder farmers in West Africa: a stated choice modelling - Ouedraogo, Adama; Ouedraogo, Mathieu; Egyir, Irene S.; Läderach, Peter; Mensah-Bonsu, Akwasi; Jatoe, John Baptist D. (Frontiers Media, 2025)
This study investigates the preferences of rainfed farmers in West Africa for bundled agroclimate services, addressing challenges posed by climate variability and limited purchasing power. With various startups offering digital communication channels, credit, and insurance services, farmers often struggle to afford individual services, necessitating coherent service packages. The research aims to identify the most preferred attributes of agroclimate services and predict how increasing climate variability affects farmers' choices. Using a Choice Experiment and Mixed Logit model, data was collected from 1,212 farmers across four West African countries (Ghana, Senegal, Mali and Burkina Faso). The findings reveal that the most preferred service bundle (Bundle 4), which includes daily weather forecasts, seed advisories, and drought insurance, garnered a preference of 45%. In contrast, Bundle 0, which lacks these features, was selected by only 22% of farmers. Notably, the introduction of a USD 1,000 credit option increased the likelihood of selecting preferred bundles by 39%. Additionally, 62% of farmers indicated that weather-based information is a critical factor in their decision-making. Access to agricultural credit significantly influenced choices, with a 17% increase in the likelihood of selecting preferred bundles when credit was available. The study underscores the importance of designing comprehensive service packages that cater to farmers' specific and urgent needs. It highlights the necessity for partnerships among service providers to improve the delivery of these essential services. By showing the agroclimate service bundling power, the study provides valuable insights for policymakers and stakeholders to support agricultural development and sustainability in West Africa